Antimicrobial resistance in Galapagos tortoises as an indicator of the growing human footprint. (1st September 2021) - Nieto-Claudin, Ainoa; Deem, Sharon L.; Rodríguez, Casilda; Cano, Santiago; Moity, Nicolas; Cabrera, Freddy; Esperón, Fernando
Abstract: Antimicrobial resistance has become one of the main public health threats worldwide with anthropogenic activities driving the spread of resistance. Understanding and combatting the spread of resistant bacteria is a top priority for global health institutions, and it is included as one of the main goals of the One Health initiative. Giant tortoises ( Chelonoidis spp.), some of the most iconic species on Earth, are widely distributed across the Galapagos archipelago and are thus perfect candidates to test the hypothesis that wildlife species in the Galapagos carry antimicrobial resistant genes (ARGs) associated with human activities. We sampled a total of 200 free-living Galapagos tortoises from western Santa Cruz Island ( C. porteri ), the most human-populated island of the archipelago, and 70 tortoises ( C. vandenburghi ) from the isolated Alcedo Volcano on Isabela Island, a natural area with minimal human presence. Fecal samples were analyzed by quantitative PCR for a panel of 21 ARGs conferring resistance for eight antimicrobial classes. We found ARGs in both Santa Cruz and Alcedo Volcano giant tortoises; however, both qualitative and quantitative results showed higher loads of ARGs in tortoises inhabiting the human modified environments of Santa Cruz. Moreover, Santa Cruz tortoises sampled in higher human-modified landscapes (i.e., farmlands and urban areas) presented a higher number of ARGs, antimicrobial classes, and multi-resistant microbiomes than those from less anthropized areas within the same island. Our findings suggest that human activities in Galapagos have a negative impact on ecosystem health through ARG dispersal. This research highlights a new threat for the health and conservation of the unique wildlife of the Galapagos, their ecosystems, and the humans inhabiting this World Heritage Site. Our recommendation to local policy makers is to control and reduce the use of antibiotics in both human and animal health, thus helping enforce antimicrobial regulations. Graphical abstract: Image 1 Highlights: Anthropogenic activities are associated with levels of ARG prevalence in Galapagos. Galapagos tortoises from Santa Cruz Island have a higher prevalence of ARGs than Isabela Island. Galapagos tortoises may act as good sentinels of ecosystem health. Abstract : Anthropogenic activities are associated with higher levels of antimicrobial resistant genes in Galapagos giant tortoises.